Marshall syndrome: Further evidence of a distinct phenotypic entity and report of new findings. Issue 10 (29th July 2014) - Khalifa, O.; Imtiaz, F.; Ramzan, K.; Allam, R.; Hemidan, A. Al‐; Faqeih, E.; Abuharb, G.; Balobaid, A.; Sakati, N.; Owain, M. Al‐
Abstract: Marshall syndrome and type II Stickler syndrome are caused by mutations in COL11A1, which codes for the proα1chain of collagen XI. Collagen XI is a minor fibrillar collagen co‐expressed with collagen II in cartilage and the vitreous of the eye. Characteristic features of Marshall syndrome include midfacial hypoplasia, high myopia, and sensorineural‐hearing deficit. Deletions, insertions, splice site, and missense mutations in COL11A1 have been identified in Stickler syndrome and Marshall syndrome patients. In this study, we describe the clinical presentations of seven patients with Marshall syndrome from three unrelated Saudi families, inherited as autosomal dominant (two families) and autosomal recessive (one family). Cardinal clinical features of Marshall syndrome are manifested in all patients. One patient had ectodermal abnormalities. Mutations (c.2702G > A in exon 34, IVS50 + 1G > A, and IVS50 + lG > C) were identified in COL11A1 in affected members. Interestingly, the first report of autosomal recessive Marshall syndrome was from Saudi Arabia caused by the same mutation (c.2702G > A, p.Gly901Glu) as in one of our families. This study depicts detailed phenotypic and genetic description of dominant and recessive forms of Marshall syndrome due to COL11A1 mutations. © 2014 Wiley Periodicals, Inc.